Titania/Electro-Reduced Graphene Oxide Nanohybrid as an Efficient Electrochemical Sensor for the Determination of Allura Red - Guangli Li; Jingtao Wu; Hongguang Jin; Yonghui Xia; Jun Liu; Quanguo He; Dongchu Chen (Nanomaterials, 2020)
Titania/electro-reduced graphene oxide nanohybrids (TiO2/ErGO) were synthesized by the hydrolysis of titanium sulfate in graphene oxide suspension and in situ electrochemical reduction. It provides a facile and efficient method to obtain nanohybrids with TiO2 nanoparticles (TiO2 NPs) uniformly coated by graphene nanoflakes. TiO2/ErGO nanohybrids were characterized by transmission electron microscopy, X-ray diffraction, cyclic voltammogram, and electrochemical impedance spectroscopy in detail. Compared with pure ErGO and TiO2 NPs, TiO2/ErGO nanohybrids greatly enhanced the electrocatalytic activity and voltammetric response of Allura Red. In the concentration range of 0.5−5.0 μM, the anodic peak currents of Allura Red were linearly correlated to their concentrations. However, the linear relationship was changed to the semi-logarithmic relationship at a higher concentration region (5.0−800 μM). The detection limit (LOD) was 0.05 μM at a signal-to-noise ratio of 3. The superior sensing performances of the proposed sensor can be ascribed to the synergistic effect between TiO2 NPs and ErGO, which provides a favorable microenvironment for the electrochemical oxidation of Allura Red. The proposed TiO2/ErGO/GCE showed good reproducibility and stability both in determination and in storage, and it can accurately detect the concentration of Allura Red in milk drinks, providing an efficient platform for the sensitive determination of Allura Red with high reliability, simplicity, and rapidness.